Inflation and relative price asymmetry - Attila Ratfai (European Central Bank (ECB), 2004)
By placing store-level price data into bivariate Structural VAR models of inflation and relative price asymmetry, this study evaluates the quantitative importance of idiosyncratic pricing shocks in short-run aggregate price change dynamics. Robustly to alternative definitions of the relative price, identification schemes dictated by two-sided (S,s) pricing theory and measures of asymmetry in the relative price distribution, idiosyncratic shocks explain about 25 to 30 percent of the forecast error variance in inflation at the 12-month horizon. While the contemporaneous correlation between inflation and relative price asymmetry is positive, idiosyncratic shocks lead to a substantial build-up in inflation only after two to five months following the initial disturbance.
Keywords: E31; 330; inflation; Relative Price; Pricing; Structural VAR